Select the optimal project by using two methods of analytic hierarchy and goal programming - Razooqee, Mohamed Naji; Ashour, Marwan Abdul Hameed (Journal of Economics and Administrative Sciences, 2020)
The aim of this research is to solve a real problem in the Department of Economy and Investment in the Martyrs establishment, which is the selection of the optimal project through specific criteria by experts in the same department using a combined mathematical model for the two methods of analytic hierarchy process and goal programming, where a mathematical model for goal programming was built that takes into consideration the priorities of the goal criteria by the decision-maker to reach the best solution that meets all the objectives, whose importance was determined by the hierarchical analysis process. The most important result of this research is the selection of the second project (constructing a cultural centre in Sadr City) as the best alternative out of seven projects. Also, the possibility of applying this model to solve multi-criteria decision-making problems in many institutions and companies was reached.